PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT SIDOMUNCUL PUPUK NUSANTARA KABUPATEN SEMARANG - Nurul Fatima Purwanto; Sandi - Supaya; Suwardi - Suwardi (Admisi dan Bisnis, 2016)
This research was aimed to know theinfluence of financial compensation and nonfinancial compensation on employee’sworking productivity at PT Sido MunculPupuk Nusantara Kabupaten Semarang.The methods of data collection were interviewand questionnaire completion. The sample ofthis research were 50 respondents andanalytical method used were the validity test,reliability test, multiple linear regressionmethod, t-test, and F-test.The result of regression analysis indicatedthat financial compensation and non financialcompensation had positive influence onemployee’s working productivity. Based on ttest result, it indicated that financialcompensation and non financialcompensation had positive significantinfluence on employee’s working productivity.Based on F test, independent variablessimutaneuosly influence the employee’sworking productivity significantly, withcoeficient of determination (R2) of 0,531. Thismeant that 53,1% of employee’s workingproductivity could be explained by variablesof financial compensation and non financialcompensation, while remaining 46,9% wasinfluenced by other variables which were notobserved.